2013
DOI: 10.1002/ccd.24897
|View full text |Cite
|
Sign up to set email alerts
|

One‐year head to head comparison of the neointimal response between sirolimus eluting stent with reservoir technology and everolimus eluting stent

Abstract: The NEVO stent with a reservoir technology seems to exhibit more neointimal proliferation as compared to Xience stent. The findings of our study, which currently represent the unique data existing on this reservoir technology, would need to be confirmed in a large population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Consequently, newer DES strive to improve vascular healing while inhibiting the physiological repair processes that are common to any foreign implant . The use of a reservoir on a stent along with a biodegradable polymer is appealing as strategy to combat ST because this construction is expected to minimize vessel wall inflammation. The FIREHAWK® (MicroPort Medical, Shanghai, China) biodegradable polymer sirolimus‐eluting stent (SES) is a novel abluminal groove‐filled biodegradable poly‐lactic acid (PLA) polymer DES with specific targeting of sirolimus release.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, newer DES strive to improve vascular healing while inhibiting the physiological repair processes that are common to any foreign implant . The use of a reservoir on a stent along with a biodegradable polymer is appealing as strategy to combat ST because this construction is expected to minimize vessel wall inflammation. The FIREHAWK® (MicroPort Medical, Shanghai, China) biodegradable polymer sirolimus‐eluting stent (SES) is a novel abluminal groove‐filled biodegradable poly‐lactic acid (PLA) polymer DES with specific targeting of sirolimus release.…”
Section: Introductionmentioning
confidence: 99%
“…These results should be, therefore, taken into account for future stent design, because polymer-free products are still in development. In light of our data, new drugs, whose elution from the stent platform is not much dependent on a polymer or reservoir technology, 12,13,36 could probably still represent 2 interesting fields of innovation in PF-DES development.…”
Section: Discussionmentioning
confidence: 83%
“…Previous OCT studies indicated an increase in the neointimal volume in durable polymer sirolimus eluting stents and BP-DES from 6 to 12 months post implantation [17,18]. Nonetheless, the differences were small and did not affect the strut coverage.…”
Section: Discussionmentioning
confidence: 88%